Parsons on Pigs and Acorns* - Gade, Daniel W. (Geographical Review, 2010)
Many articles in the Geographical Review hold stories that resonate in the history of geography only when the passage of time provides the necessary detachment to put these accounts into a context of larger signiﬁcance. The circumstances behind the selection of a particular topic, vicissitudes of the research phase, personality of the author, and exchanges during the editorial process that bring it to publication together provide insight into the diﬀerent layers of geographical scholarship. To all that can be added another dimension: explaining the impact that the piece of writing has had on individuals who have read it. One article in the Geographical Review profoundly aﬀected the formation of my geographical imagination. It did so without appealing to any theory, showcasing some dazzling new technique, harboring an advocacy agenda, or exhorting the reader in any way. Now, nearly half a century after its publication, this text opened another level of reﬂection about its content, author, journal, editor, and changes in the place that was under study.
Keywords: acorns; Dehesa; Iberian ham (voyant); Oak woodland; pigs